Lipoprotein apheresis influences monocyte subpopulations. (November 2017) - Jellinghaus, S.; Reich, C.; Schatz, U.; Tselmin, S.; Ibrahim, K.; Pfluecke, C.; Schauer, A.; Bornstein, S.R.; Hohenstein, B.; Strasser, R.H.; Julius, U.; Poitz, D.M.
Abstract: Background: Monocytes can be differentiated into subpopulations depending on their expression profile of CD14 and CD16. CD16-positive monocytes are associated with coronary artery disease. Up to now, no data exist about the effect of lipoprotein apheresis (LA) on the distribution of monocyte subpopulations. Methods: 80 patients who underwent LA at the University Hospital Dresden were included in the study. 8 out of the 80 LA patients received LA for the first time at the time point of blood analysis. Six different methods of LA were used (H.E.L.P. n = 8; Liposorber D n = 10; LF n = 14; DALI n = 17; MONET n = 11; Therasorb ® LDL n = 12). Blood samples were taken immediately before and after LA and analyzed for CD14 and CD16 expression on monocytes. A total of 42 patients with cardiovascular risk factors but no indication for LA served as control group. Results: The composition of monocyte-population was analyzed in regard to the 3 subpopulations. After LA, an increase in classical monocytes (CD14 ++ CD16 − ) (93.3% vs. 93.9%, p < 0.01) and a decrease in non-classical monocytes (CD14 + CD16 + ) (1.5% vs 1.0%; p < 0.001) were observed. LA did not change the amount of intermediate monocytes (CD14 ++ CD16 + ) (5.3% vs. 5.1%). Two methods (MONET and Therasorb ® LDL) did not influence the distribution of monocyte subpopulations. Interestingly, patients with LDL-C above 2.5 mmol/l prior LA showed increased amounts of intermediate monocytes. Conclusion: The distribution of monocyte populations is influenced by LA but depends on the distinct method of LA. Influences of LA were mainly observed in the content of classical and non-classical monocytes, whereas the intermediate monocyte population remained unaltered by LA.